"All for One" experiences of interprofessional team members caring for older adults: A metasynthesis. (28th November 2019) - Montano, Anna‐Rae
Abstract: Background: There is some evidence that healthcare professionals prefer an interprofessional approach to care and this approach is of particular importance to older people due to their complex needs and multitude of chronic conditions. Objective: This metasynthesis aimed to synthesise and unearth new understandings of the experiences of interprofessional team members that are caring for older people from a variety of qualitative studies. Design: This review is designed as a metasynthesis based on the method put forth by Noblit and Hare for synthesising qualitative research. Data sources: A search for qualitative and mixed methods articles that included healthcare professionals' experiences of caring for older people as a member of an interprofessional team was conducted via an electronic database search of CINAHL, PubMed, SCOPUS and PsycINFO. Review methods: The inclusion criteria were as follows: (a) the method of the study was qualitative or included a qualitative component, (b) an interprofessional team cared for an older person, (c) data regarding interprofessional team members' experiences were gathered, (d) published in English and (e) between the period of 2000 and 2019. Key metaphors were extracted from the data and juxtaposed until themes emerged. Results: A total of 1807 full‐text articles were retrieved and screened via their titles and abstracts. Nine studies were included in this metasynthesis based upon full‐text relevance and meeting the inclusion criteria. Six themes emerged describing the experience of interprofessional team members caring for older people: All for One: Unifying the Team for a Meaningful Purpose; The Cast; A Shared Vocabulary; Collaboration and Integration; A Functional‐Dysfunctional Family and Appreciate the Lifeworld. Team members appreciated this model of care. Conclusions: The emergent themes suggest potential buy‐in from interprofessional team members to this care model for older people. Nursing can assert their unique knowledge and practice into the role as the team leader to mitigate potential barriers and team conflicts. Implications for practice: Interprofessional team members caring for older people can improve their experience. Improved experiences for interprofessional team members can lead to better care for older people. Professionals need specialized training prior to practicing interprofessionally.